The Role of Kinesiotherapy in Enhancing Physical Performance and Self-Esteem: A Prospective Observational Study in Obese Adolescents - Cristina Popescu; Daniela Matei; Rodica Trăistaru (Balneo and PRM Research Journal)
Obesity is a multifactorial chronic condition characterized by excessive fat accumulation, which adversely affects health and quality of life. This prospective observational study aimed to evaluate the impact of a 9-month tailored kinesiotherapy program on physical performance, body composition, and self-esteem in overweight and obese adolescents. Participants were divided into a study group (SG, n=40) and a control group (CG, n=40). The SG engaged in individualized kinesiotherapy sessions, while the CG maintained their usual activities. Both groups received education on the 5-2-1-0 rule for obesity prevention and management. Results indicated significant improvements in the SG, including enhancements in the 6-minute walk distance (6MWD), Timed Up-and-Go test (TUG), and Rosenberg Self-Esteem Scale (all p < 0.001). Notably, BMI and body fat percentage decreased significantly in the SG compared to the CG. Regression analysis revealed strong correlations between body composition, physical performance, and self-esteem improvements, particularly in girls and rural participants, highlighting the intervention's adaptability and effectiveness. Although limited by a relatively small sample size, short duration, and variability in adherence tracking, the study highlights the essential role of individualized physical activity programs in improving health outcomes. In conclusion, the findings from our study emphasize the significant role of individualized kinesiotherapy programs in improving physical and psychological health outcomes in overweight/obese adolescents. By integrating instrumental assessments, such as the BTS system, with subjective evaluations like PAQ-A and the Rosenberg scale, our study high-lights the multifaceted impact of physical activity on this vulnerable population